Thermal conductivity of GaN single crystals: Influence of impurities incorporated in different growth processes - Rounds, Robert; Sarkar, Biplab; Sochacki, Tomasz; Bockowski, Michal; Imanishi, Masayuki; Mori, Yusuke; Kirste, Ronny; Collazo, Ramón; Sitar, Zlatko (Journal of applied physics, 2018)
The thermal conductivity of GaN crystals grown by different techniques is analyzed using the 3ω method in the temperature range of 30 K to 295 K. GaN wafers grown by the ammonothermal method show a significant variation in thermal conductivity at room temperature with values ranging between 164 W m−1 K−1 and 196 W m−1 K−1. GaN crystals produced with the sodium flux and hydride vapor phase epitaxy methods show results of 211 W m−1 K−1 and 224 W m−1 K−1, respectively, at room temperature. Analysis using secondary ion mass spectrometry indicates varying amounts of impurities between the respective crystals and explains the behavior of thermal conductivity trends in the samples. The observed difference between thermal conductivity curves suggests that scattering of phonons at point defects dominates the thermal conductivity of GaN within the investigated temperature range. Deviations of model curves from thermal conductivity measurements and disparities between modelled characteristic lengths and actual sample thicknesses indicate that phonon resonances are active in GaN.